The Antecedents of Thriving at Work: A Meta-Analytic Review - Liu, Danping; Zhang, Siwen; Wang, Yanling; Yan, Yufei (Frontiers in Psychology, 2021)
This study is a systematic and comprehensive meta-analysis of the relationship between thriving at work and its antecedents. The antecedents in terms of the characteristics of unit contextual features, the resources produced at work, agentic work behaviors and personality traits, are illustrated, based on Spreitzer socially embedded model of thriving, and research. Additionally, we examine possible cultural influence on the relationship between thriving and its antecedents, at various levels of individualistic culture. Based on 67 independent samples (N = 28,097), our findings reveal correlations between thriving at work, and the antecedents such as those in the form of unit contextual features, the resources produced at work, agentic work behaviors, and personality traits. Furthermore, we find that individualism moderate the relationships between certain antecedents and thriving at work. Finally, we discuss the theoretical and practical implications of this study, as well as directions for future research.